Fabrication and physicochemical characterisation of novel pimozide loaded PLGA nanoparticles - Ahmed M Faheem; Amal Ali Elkordy; Nazim Uddin (University of Huddersfield Press, 2019)
Cancer has always been a big concern for human health. There is always an increased need for fabrication of newer drugs or repurposing the existing drugs to treat cancer. Apart from being an antipsychotic agent, pimozide has already shown its anticancer activity against various cancers in several studies. The aim of the present study was to fabricate pimozide loaded PLGA nanoparticles and hence characterize them. Single emulsion and microfluidic techniques were used to prepare nanoparticles. Physicochemical properties such as particles size, shape, surface charge, and encapsulation efficiency were investigated. Results showed that the nanoparticles were in average size distribution of 200-300 nm, spherical in shape and negatively charged. Additionally, high encapsulation efficiency (50-89%) makes these nanoparticles potential drug delivery systems to target cancer cells.